Sistem Pengukuran Kinerja dan Dampaknya terhadap Kinerja pada Unit Pemerintah Daerah di Indonesia - Anita Primastiwi; Taufan Adi Kurniawan; Sri Kiswati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
The Indonesian government, through the Ministry of Administrative and Bureaucratic Reform of the Republic of Indonesia, has regulated the accountability of public sector organization management through PermenPANRB Nomor 88 Tahun 2021. However, Government Agency Performance Accountability System (SAKIP) evaluation results for over the past 10 years show an average SAKIP score less than 75 out of 100, which is certainly far from expectations. This study attempts to analyze one of the reasons for the low SAKIP score by focusing on contractibility to determine the clarity of organizational goals so that organizational performance is easier to achieve and can satisfy all stakeholders. The results show that contractibility has a positive influence on organizational performance, but contractibility does not moderate the use of performance measurement systems for incentive purposes and exploratory purposes. The existence of contractibility, such as clear objectives, measurable performance, and the actor's knowledge of the transformation process, makes it easier for employees to complete their tasks. Meanwhile, contractibility does not moderate the use of performance measurement for incentive and exploratory purposes due to low levels of incentives, low levels of contractibility, and a top-down organizational structure that does not support feedback for exploratory purposes.